Neurologic Medical Device Overview for Pathologists. (April 2019) - Cramer, Sarah D.; Lee, Juliana S.; Butt, Mark T.; Paulin, Jaime; Stoffregen, William C.
Thorough morphologic evaluations of medical devices placed in or near the nervous system depend on many factors. Pathologists interpreting a neurologic device study must be familiar with the regulatory framework affecting device development, biocompatibility and safety determinants impacting nervous tissue responses, and appropriate study design, including the use of appropriate animal models, group design, device localization, euthanasia time points, tissue examination, sampling and processing, histochemistry and immunohistochemistry, and reporting. This overview contextualizes these features of neurologic medical devices for pathologists engaged in device evaluations.